2020
DOI: 10.1242/jcs.253906
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for prominin-1 and photoreceptor cadherin in outer segment disc morphogenesis in CRISPR-altered X. laevis

Abstract: Mutations in prominin-1 (prom1) and photoreceptor cadherin (cdhr1) are associated with inherited retinal degenerative disorders but their functions remain unknown. Here, we used CRISPR-Cas9 to generate prom1-null, cdhr1-null, and prom1 plus cdhr1 double-null Xenopuslaevis and then documented the effects of these mutations on photoreceptor structure and function. Prom1-null mutations resulted in severely dysmorphic photoreceptors comprising overgrown and disorganized disc membranes. Cone outer segments were mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The incremental array of structural defects observed in young mice suggests a sequence of events leading to pathology in these and potentially other PRPH2 mutant mice. As discs remain open for an abnormally long period of time, they occasionally incorporate more than a normal amount of membranous material delivered to the outer segment, causing disc overgrowth comparable to that observed in other models (e.g., Yang et al, 2008;Schietroma et al, 2017;Sharif et al, 2018;Spencer et al, 2019;Carr et al, 2021). This disc overgrowth can become uncontrolled, leading to the formation of "membrane whorl" structures described for other mutations in PRPH2 (Hawkins et al, 1985;Tam et al, 2004;Chakraborty et al, 2016Chakraborty et al, , 2020Lewis et al, 2020) and other proteins (LaVail et al, 1972;Narfström and Nilsson, 1989;Leon and Curtis, 1990;White et al, 1993;Stiemke et al, 1994;Jablonski et al, 1999;Gao et al, 2002;Yefimova et al, 2002;Duncan et al, 2003;Rice et al, 2004;Lu et al, 2019;Spencer et al, 2019;Ying et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
“…The incremental array of structural defects observed in young mice suggests a sequence of events leading to pathology in these and potentially other PRPH2 mutant mice. As discs remain open for an abnormally long period of time, they occasionally incorporate more than a normal amount of membranous material delivered to the outer segment, causing disc overgrowth comparable to that observed in other models (e.g., Yang et al, 2008;Schietroma et al, 2017;Sharif et al, 2018;Spencer et al, 2019;Carr et al, 2021). This disc overgrowth can become uncontrolled, leading to the formation of "membrane whorl" structures described for other mutations in PRPH2 (Hawkins et al, 1985;Tam et al, 2004;Chakraborty et al, 2016Chakraborty et al, , 2020Lewis et al, 2020) and other proteins (LaVail et al, 1972;Narfström and Nilsson, 1989;Leon and Curtis, 1990;White et al, 1993;Stiemke et al, 1994;Jablonski et al, 1999;Gao et al, 2002;Yefimova et al, 2002;Duncan et al, 2003;Rice et al, 2004;Lu et al, 2019;Spencer et al, 2019;Ying et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
“…The expression of Edn2 has also been shown to be upregulated in other mouse models of RP ( Bramall et al, 2013 ), including retina-specific Cdhr1 -KO mice ( Rattner and Nathans, 2005 ), with Prom1 and Cdhr1 having been found to interact with each other ( Yang et al, 2008 ). Although a recent study demonstrated different phenotypes for the Prom1- and Cdhr1 -mutant retinas ( Carr et al, 2021 ), the functions of these two proteins may be mediated by similar signalling pathways.…”
Section: Discussionmentioning
confidence: 94%
“…Although a recent study demonstrated different phenotypes for the Prom1and Cdhr1-mutant retinas (Carr et al, 2021), the functions of these two proteins may be mediated by similar signalling pathways.…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to cone phototransduction proteins, we also examined the localization of two structural proteins, peripherin-2 (Prph2) and prominin-1 (Prom1). Both Prph2 and Prom1 are important for disk morphogenesis in rods and cones ( 11 17 ). As expected, Prom1 was normally restricted at the base of both ROS and COS in WT mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%